THE IMPACT OF CHRONICALLY LOW-DOSE IONIZING IRRADIATION ON THE IMMUNE SYSTEM, MECHANISMS OF NEUROENDOCRINE REGULATION AND CERTAIN BIOCHEMICAL INDICATORS IN ANIMALS UNDER THE CONDITIONS OF RADIATION CONTAMINATED AREAS OF UKRAINE - Kurman, A.; Karisheva, L.; Shcherbyna, O.; Chyzhevskyi, I. (Scientific Progress & Innovations, 2021)
The agrarian sector of Ukraine`s economy is quite confidently coming to the fore in the structure of the country`s export industries. If the economical and medical-biological situation of the society stabilize, undoubtedly, the agricultural production will be the moving force of Ukraine`s development. However, large areas of farm lands in some regions of Ukraine have significant residual radioactive pollution as a result of Chernobyl accident isotopes. The initial post-accident severity of the problem has largely been removed owing to the natural breakdown of active isotope nuclei. This made it important to redirect the efforts of radiobiologists from studying the patterns of disorders and pathologies under high radiation exposure with further development of methods and measures to combat destructive processes, to research and explain the organism response to harmful long-term low-intensity radiation effects on animals and humans. The scientific community has already created sufficiently extensive network of research centers solving low-dose radiation issues. They also have specialized information resources, such as the International Journal of Low Radiation. However, radiobiologists from Ukraine are not able to actively cooperate within this system due to insufficient state funding of research activities. Unfortunately, foreign scientists are not particularly interested in studying such objects as farm animals. Therefore, at present, the general array of experimental and monitoring results does not provide a sufficiently complete picture of the changes in the homeostasis of irradiated individuals. Generally, the available data show that under these circumstances, the occurring damages are related to the direct energy uptake in critical targets and indirect upsetting due to certain changes in physical, chemical and biochemical processes at the molecular-cellular level. In particular, there is an increase of lipid peroxidation and reduction of endogenous multicomponent antioxidant system activity. It has been found that during prolonged radiation exposure in small doses, the processes of hormonal homeostasis imbalance take place, which are associated with the imbalance in non-specific mechanisms of neuroendocrine adaptation process regulation. The main role in their implementation belongs to neurotransmitters, which, in addition to controlling the processes of excitation and inhibition of nerve cells, also control various mechanisms of the body, including the neuroendocrine system. These neurotransmitters are involved in regulating the secretion of hypothalamic factors and pituitary hormones. The studies of the functional state of the hypothalamic-pituitary-adrenocortical system with prolonged low dose radiation exposure have allowed to reveal its sensitivity to internal irradiation in small doses. Under the influence of long-term low-intensity irradiation factor in animals there are not only certain hormonal balance changes but there are also alterations in the immune system functioning. The formation of pathological changes in the concentration and distribution of biochemical compounds and metabolic processes also take place together with immunity reduction. Quantitative assessment of the biological effects of low-dose chronic irradiation of higher organisms remains one of the most controversial and unexplained problems in agricultural radiobiology.